A comparison study of different physical treatments on cartilage matrix derived porous scaffolds for tissue engineering applications - Moradi, A.; Pramanik, S.; Ataollahi, F.; Khalil, A.A.; Kamarul, Tunku; Pingguan-Murphy, Belinda (IOP Publishing Ltd, 2014)
Native cartilage matrix derived (CMD) scaffolds from various animal and human sources have drawn attention in cartilage tissue engineering due to the demonstrable presence of bioactive components. Different chemical and physical treatments have been employed to enhance the micro-architecture of CMD scaffolds. In this study we have assessed the typical effects of physical cross-linking methods, namely ultraviolet (UV) light, dehydrothermal (DHT) treatment, and combinations of them on bovine articular CMD porous scaffolds with three different matrix concentrations (5%, 15% and 30%) to assess the relative strengths of each treatment. Our findings suggest that UV and UV-DHT treatments on 15% CMD scaffolds can yield architecturally optimal scaffolds for cartilage tissue engineering.